The Influence of Brand Image, Information Quality and Celebrity Endorsers on Purchasing Decisions on Instragram - Frans Sudirjo; Ridwansyah Ridwansyah; Tessa Handra; Maria Assumpta Wikantari; Aat Ruchiat Nugraha (International Journal of Economics Development Research (IJEDR), 2023)
Nowadays, the development of technology is increasingly advanced, many business people use digital platforms as marketing strategy tools. Social media is now used to introduce a product or service from a company, organization, or government. Along with the development of technology and information, nowadays many online shops have sprung up in various groups, from teenagers to adults. One of the local companies that uses Instagram social media to spread information about their company's products is Erigo. This study aims to analyze and examine the influencing factors of brand image, information quality and celebrity endorser on purchasing decisions of Erigo Brand products in Instagram. The method of research is using the quantitative and regression analysis. The sampling method used purposive sampling and the number of samples used in this study amounted to 80 respondents The source was the distribution of online questionnaires via WhatsApp to customers who had purchased Erigo brand products through Instagram. The data were analyzed with IBM SPSS version 22 and was carried out by several tests such as validity test, reliability test, classic assumption test, linear regression analysis and coefficient of determination test. The results of this study indicate that the brand image, information quality and celebrity endorser have a significant and positive effect partially or simultaneously on purchasing decisions of Erigo brand products. Meanwhile, brand trust can provide the most dominant influence on purchasing decisions of Erigo brand products.